Elevated risk of venous thromboembolic events in patients with inflammatory myopathies - Nowak, Michał (Vasc Health Risk Manag, 2016)
Venous thromboembolism (VTE) is a multifactorial disease manifesting as either deep vein thrombosis or pulmonary embolism. Its prevalence makes VTE a significant issue for both the individual – as a negative factor influencing the quality of life and prognosis – and the society due to economic burden. VTE is the third most common vascular disorder in Western countries, after myocardial infarction and stroke, making it a major cause of in-hospital mortality, responsible for 5%–10% of hospital deaths. Despite many studies conducted, only 50%–60% provoking factors have been identified, while the remaining 40%–50% have been classified as idiopathic or unprovoked. Chronic inflammatory disorders, with their underlying prothrombotic state, reveal an increased risk of VTE (six to eight times) compared with the general population. Among the inflammatory disorders, we can identify inflammatory myopathies – a group of rare, chronic diseases featuring weakness and inflammation of muscles with periods of exacerbation and remission; their main classes are polymyositis and dermatomyositis. The objective of this review is to emphasize the need of VTE prophylaxis in individuals with inflammatory myopathies in order to reduce morbidity and mortality rates among those patients and improve their quality of life and prognosis.